Optimization of rhamnolipid production using oil extracted from oil palm biomass as carbon sources by Pseudomonas aeruginosa strain K - Zahraa' Nur Sabrina Mohd Mubarak (2015)
ABSTRACT
Rhamnolipids are one of the important biosurfactants that are useful in many industries like pharmaceutical, bioremediation and agriculture. Pseudomonas aeruginosa is one of the microorganisms that can produce rhamnolipid. The aim of this study is to test the ability of our P. aeruginosa strain K to utilize oil palm biomasses as the substrate to produce rhamnolipids. Based on the qualitative test on cetyltrimethyl ammonium bromide agar, P. aeruginosa strain K was identified as a rhamnolipids producer. The emulsification index (E₂₄) of the rhamnolipids produced was 56.80%. Oil from three types of oil palm biomasses; palm oil mill effluent (POME), decanter cake (DC) and mesocarp were extracted and used as the substrates for rhamnolipids production. Oil from POME gave the highest E₂₄ value (43.02%). The rhamnolipids can be detected after 48 hours of incubation time with an E₂₄ value of 41.42% when POME oil was used as a carbon source. After 48 hours of incubation time, 1% concentration of oil from POME produced 45.97% of E₂₄ value. This research showed that oil palm biomasses could be used to produce rhamnolipids from Pseudomonas aeruginosa strain K. This offers an opportunity to produce rhamnolipids at low cost and safer manner which meets industrial and ecological needs.
Project paper B.S.(Hons.) Microbio. - Universiti Putra Malaysia, 2015.